EFEKTIVITAS KEBIJAKAN PEMERINTAH DAERAH DALAM UPAYA PENANGGULANGAN PERMASALAHAN HIV/AIDS DI KOTA BANDUNG TAHUN 2023 - Iskandar, Kirana Safira Sholehah; Muradi, Muradi; Mulyawan, Rahman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The issue of HIV/AIDS is a complex and multidimensional public health concern with serious implications for development and societal well-being. Bandung City has recorded the highest number of HIV/AIDS cases in West Java Province, despite the local government having enacted policies through Regional Regulation Number 12 of 2015. This study aims to assess the effectiveness of local government policies in addressing HIV/AIDS in Bandung City in 2023. This research employs a qualitative method with a descriptive approach. Data were obtained through documentation and interviews with parties involved in policy implementation. The findings indicate that the implemented policies have not been fully effective in meeting community needs, as several issues persist regarding the accuracy of the program, implementers, targets, environment, and implementation process. The study recommends strengthening intersectoral coordination, improving the capacity of policy implementers, and promoting community-based participatory approaches to enhance the success of local HIV/AIDS prevention and control programs.